The Relationship between Perceived Social Support and Quality of Sleep in Nursing Students - Rambod M; Ghodsbin F; Beheshtipour N; Raieyatpishe AA; Mohebi Noubandegani Z; Mohammadi-Nezhad A (Iran University of Medical Sciences, 2012)
Background & Aims : quality of sleep could be useful in health promotion and improvement of quality of life in student. Some psychosocial factors such as social support might affect the quality of sleep. Accordingly, the aim of this study was to determine the relationship between perceived social support and quality of sleep in nursing students.   Material & Methods : It was a descriptive correlational study. Eighty seven nursing students of Shiraz University of Medical Sciences recruited by census, during school year of 2010-2011. The Persian versions of the "Personal Resources Questionnaire 85 (PRQ85)" and "Pittsburgh Sleep Quality Index (PSQI)" were used to evaluate the participants' perceived social support and sleep quality. Data were analyzed using SPSS-PC (v. 15) by chi-square test, and Spearman's rho correlation coefficients.   Result : Most of the students had high levels of perceived social support (% 49.4) and poorer quality of sleep (% 61.0). Statistically significant relationships were found between social support and financial status ( c 2 =7.74, p=0.02) and place of residence ( c 2 =9.19, p=0.007). Third and fourth year nursing students had poorer sleep quality. In addition, there were a statistically significant relationship between perceived social support and quality of sleep in nursing students (r =-0.33, p= 0.01).   Conclusion : Considering the relationship between social support and sleep quality among nursing students, managers of the nursing school and families could improve their sleep quality by providing the required social support.  Received: 22 Oct 2012   Accepted: 4 Jan 2013